IGNITING BURNING WAVE IN A SMALL NUCLEAR REACTOR SUITABLE FOR REMOTE AREAS IN MONGOLIA - A, Tsendsuren.; B, Munkhbat.; S, Odmaa. (Mongolian Journal of Engineering and Applied Sciences, 2020)
In Mongolia, energy demand is increasing rapidly and installed capacity cannot keep up the demand due to a weak condition of both electricity access and grid structure. According to a survey, primary electricity demand by 2025 would be higher in the central region and tend to increase in other regions. Full coverage of the country by grid extension is difficult from a technical as well as an economic perspective because of high investment costs and high electrical loss over long distances, and low demand in the remote regions. Therefore, small power systems are suitable in remote regions and typical large-size power systems are not a very good option. However, a small fast reactor system may be suitable, having unique characters, to reduce nuclear waste and effective use of nuclear fuel. In this study, a preliminary design study on a small breed and burn type fast reactor was carried out using continuous energy Monte Carlo code MVP/GMVP II with the JENDL-3.3 data library. In the concept of breed and burn, igniting a burning wave is an important concern. This study concerns the igniting burning wave with enriched uranium for initiating the conversion process. As seen from the result, the proposed small reactor could operate more than seventy years under breed and burn mode.